2009
DOI: 10.1354/vp.08-vp-0255-b-fl
|View full text |Cite
|
Sign up to set email alerts
|

Clara Cell Secretory Protein Is Reduced in Equine Recurrent Airway Obstruction

Abstract: Abstract. Horses are prone to recurrent airway obstruction (RAO), an inflammatory lung disease induced by repeated exposure to environmental mold, dust, and bacterial components. Active disease manifests with mucus hyperproduction, neutrophilic inflammation, bronchoconstriction, and coughing. Chronically affected animals have lung remodeling characterized by smooth muscle hyperplasia, collagen deposition, lymphoid hyperplasia, and impaired aerobic performance. Clara cell secretory protein (CCSP) counters infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…Previous studies showed that SCGB1A1 was reduced in horses with RAO compared to those without lung disease, but did not assess expression of individual genes [17]. Here, SCGB expression was compared to glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ) mRNA and 18S ribosomal RNA ( RN18S ) as internal controls.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies showed that SCGB1A1 was reduced in horses with RAO compared to those without lung disease, but did not assess expression of individual genes [17]. Here, SCGB expression was compared to glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ) mRNA and 18S ribosomal RNA ( RN18S ) as internal controls.…”
Section: Resultsmentioning
confidence: 98%
“…RAO and control horses ranged in age from 6 to 18 years and were selected according to previously established criteria [17]. Clinical challenge, pulmonary function testing (PFT), and BAL procedures were performed as described [17]. Briefly, horses were maintained outdoor to limit dust and mould exposure preceding the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to CC10, several previous investigations have demonstrated lower levels in BALF of smokers than nonsmokers [7,1114], and significantly decreased BALF CC10 levels were also detected in smokers compared with nonsmokers in a recent proteomic study [15]. Moreover, reduced production of CC10 and decreased CC10 levels in BALF appear to be features of environmentally induced lung inflammation in horses [13] and rats [14]. …”
Section: Discussionmentioning
confidence: 94%
“…Immunohistochemical analysis has evidenced the presence of cytochrome P450 (Cytochrome Proteins) (CYP) in lung cells such as: macrophages (Pavek & Dvorak, 2008), endothelium, alveolar cells types I and II, ciliated cells (Castell et al, 2005) and Non-Ciliated Bronchiolar Cell or Clara cell. Clara cells are the leading cells for xenobiotic metabolism in the lung because its profuse cytochrome P450 mono oxygenase activity (Katavolos et al, 2009). …”
Section: Lung Metabolic Active Cellsmentioning
confidence: 99%